Cloud Assisted Event Data Recorder for Four Wheelers - Dias, Nadine A; Verenkar, Prutha; Nair, Vineeth; Dessai, Priyanka; Rai, Sandesh K (International Journal of Computer Sciences and Engineering, 2019)
Over speeding is one of the major causes of road accidents all over the world. Road accidents account for more deaths than those related to different diseases put together. It has now become a necessity that we take preventive measures towards this problem. Cloud Assisted Event Data Recorder for Four Wheelers keeps check on all registered vehicles for their speed and if the vehicle is found to be over speeding an e-challan is sent to the defaulter via an email. This will considerably bring down the over speeding cases, eventually leading to lesser road accidents hence leading to safer roads. This work consists of an Event Data Recorder which is an inherent part of a vehicle sending real time data to the cloud wherein it is processed. It is a 24X7 regulating process and therefore the vehicle is monitored even in the absence of human intervention.